Names in the Mass Media Texts (Proceedings of Southern Federal University. Philology, 2019)
Elena V. Glinka (Minsk, Belarus) Precedent The proper name in the texts of the media is one of the ways to express the author’s modality, appraisal and a means of attracting the attention of the reader. Therefore, most often precedent names are found in the most significant and strong positions of the media text: in the headline set or at the end of the article. Precedents include names that are known to all (or many) representatives of the national-cultural community, as well as relevant in terms of current events. The article analyzes the texts of a number of Belarusian printed publications of 2019, where names in headings and leads are not only a means of attracting attention, but also a factor in enhancing the expressiveness of the text and expression of appreciation.Key words: precedent names, connotations, the mass media of Belarus.DOI 10.23683/1995-0640-2019-4-209-215